P2-S9.07 Economic risk factors for syphilis infection among pregnant women in rural Haiti. (10th July 2011) - Mark, J; Wesler, L; Oswald, C; Léandre, F; Nevil, P; Bertrand, D; Bertrand, J; Boehm, F; Fawzi, M C Smith
Abstract : Background: Of the 12 million global adult syphilis infections occurring globally each year, syphilis disproportionately affects women in low-income countries. WHO estimates about 80% of syphilis positive pregnancies go untreated, often in Latin America and Africa. Economic and socio-structural characteristics may explain some of the vulnerability for infection. We studied the association between social and health services factors and syphilis in Haiti, a poor country with a high burden of infection. Methods: We used data collected for a clinic-based case-control study of pregnant women attending general care women's clinics in rural Haiti from June 1999—to March 2001. Syphilis serostatus was determined by RPR test. Women were surveyed on socio-demographic and economic factors, access to healthcare, and sexual and gynaecological history. We performed multivariate analysis in SAS to identify factors associated with syphilis seropositivity and present results on two models. Results: The 596 women studied were typically young, rural, and lived in poverty. Syphilis and HIV seropositivity were 5.5% and 4.3%, respectively. In model 1 (n=396), factors associated with maternal syphilis infection were: household monthly per capita income <75 goud ($20 USD) (OR 2.4, 95% CI 0.9 to 6.6), having a 1 room house (OR 5.2, 95% CI 1.6 to 17.0), and history of prior pregnancy resulting in premature birth (OR 5.1, 95% CI 2.0 to 13.0). In model 2 (n=417), having fields where family members plant crops was a protective factor (OR 0.26, 95% CI 0.074 to 0.92), while reporting problems obtaining education (OR 3.2, 95% CI 1.1 to 7.7), <15 years of age at first intercourse (OR 2.9, 95% CI 1.1 to 7.7), history of an STD (OR=11.0, 95% CI 3.2 to 40.0), and vaginal discharge with odour (OR 3.4, 95% CI 1.1 to 11.0) were associated with maternal syphilis infection see Abstract P2-S9.07 Table 1 . Discussion: Among pregnant women in Haiti, some economic characteristics were predictors of vulnerability for syphilis infection and may help explain the inequitable distribution of syphilis disease burden. Further study is warranted to understand specific economic or other structural factors that may affect syphilis infection in women and may be amenable to intervention.